Role of growth differentiation factor-15 (GDF-15) in missed miscarriage and its relationship to oxidative stress markers - Olga G. Tishkova; Lyudmila V. Dikareva; Kristina M. Romanenko (Гинекология, 2023)
Aim. The study aimed to investigate the level of growth differentiation factor-15 (GDF-15) and its relationship to markers of oxidative stress (OS) as predictors of missed miscarriage (MM).